For Experts Only?: Access to Hospital Ethics Committees - Agich, George J. (The Hastings Center report, 1991)
How closely involved with hospital ethics committees should patients and their families become? Should they routinely have access to committees, or be empowered to initiate consultations? To what extent should they be informed of the content or outcome of committee deliberations? Seeing ethics committees as the locus of competing responsibilities allows us to respond to the questions posed by a patient rights model and to acknowledge more fully the complex moral dynamics of clinical medicine.